The effectiveness of the Barton's intervention program on reading comprehension and reading attitude of students with dyslexia - Mihandoost, Zeinab; Elias, Habibah (Mazandaran University of Medical Sciences, 2011)
Objective: The current research tested the differences in reading attitude and reading comprehension in the dyslexic students between the control group and the experimental group following the Barton intervention program. Methods: Dyslexia screening instrument and reading text were employed in order to identify dyslexic students. The population of the study included 138 dyslexic students studying in schools in Ilam, Iran. From this population, 64 students were randomly selected and assigned to an experimental group as well as a control group. The experimental group was taught for 36 sessions, using the Barton’s method at two levels, and ten lessons were provided to improve the reading skill. The reading comprehension and reading attitude instruments were employed for the measurement of the attitude and comprehension before and after the intervention program. Results: The analysis of covariance showed a significant difference between the control group and the experimental group following the Barton intervention program. Conclusion: This study showed that dyslexic students learned to read, and a more direct instruction related to decoding could influence their progress more than the general exposure to education.